Theoretical and NMR structural characterisation of a polymorphic azo dye - Rodrigues, Lígia M. (2005)
Proton and carbon-13 NMR studies in solution and carbon-13 CP-MAS NMR in the solid state of a polymorphic azo dye derived from 2-amino-5-nitrothiazole were performed and the results are discussed and compared with theoretical data from quantum chemical calculations. The polymorphism of this compound has conformational character, two conformers coexist in CDCl3 solution and in solid state, as shown by NMR.